Improving Work-Life Integration Among Emergency Room Physicians in a Level 1 Government Hospital in Jolo, Sulu: A Basis for Institutional Support Model - Tulawie, Precious Narimae; Faller, Erwin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the work-life integration of Emergency Room physicians in a Level 1 Government Hospital in Jolo, Sulu as basis for developing an institutional support model. It focused on the physician’s lived experiences, factors influencing work-life integration, challenges and barriers encountered, and recommended institutional support mechanisms. The study was anchored on the Job Demands-Resources Model, Conservation of Resources Theory, and Spillover Theory. A qualitative descriptive research design was employed using semi-structured interviews with twelve licensed Emergency Room physicians selected through purposive sampling. Data were gathered through a self-made interview guide questionnaire and analyzed using thematic analysis. Findings revealed that ER physicians experience heavy professional demands, 24-hour shifts, high patient volume, unpredictable schedules, physical fatigue, emotional strain, limited recovery time, and reduced personal and family time. Despite these difficulties, physicians demonstrated adaptive strategies such as boundary-setting, intentional time use, peer support, and meaning-making through saving lives and serving the Tausug community. Major barriers included understaffing, solo night duties, geographic isolation, long commute, limited consultant support, management-staff communication gaps, disrupted religious practice, emotional numbing, and mental health stigma. The study concluded that effective work-life integration requires balancing high job demands with adequate institutional resources. The proposed Work-Life Integration Institutional Support Model emphasizes workforce and staffing, scheduling and systems reform, wellness and emotional support, leadership responsiveness, and GIDA-specific incentives. The study aligns with SDG 3, SDG 8, and SDG 11 by supporting healthcare worker well-being, decent work conditions, and sustainable healthcare access in underserved communities. Its sustainability impact lies in strengthening institutional support, physician retention, workforce resilience, and quality emergency care delivery in a geographically isolated and disadvantaged area.
Keywords: Burnout, Emergency Room Physicians; Geographically Isolated and Disadvantaged Areas; Institutional Support Model; Jolo Sulu; Level 1 Government Hospital; Physician Well-Being; Thematic Analysis; Work-Life Integration